Hubungan asupan energi, waktu pemberian MP-ASI, dan panjang badan lahir dengan kejadian stunting pada batita di Desa Mojokerto: Studi Potong Lintang - Fitri, Windiarti Anisa; Mulyasari, Indri (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Stunting remains an unresolved nutritional problem in Indonesia, with a prevalence of 21,5% in 2023. Mojokerto Village is one of the areas with a high prevalence, reaching 30%. Factors suspected to be associated with stunting in Mojokerto Village include energy intake, timing of complementary feeding, and birth length. However, to date, no study has simultaneously examined the relationship between energy intake, timing of complementary feeding, and birth length with stunting in this area.Objectives: This study aims to investigate the relationship between energy intake, the timing of complementary feeding, and birth length with the incidence of stunting among toddlers in Mojokerto.Methods: This research employs a quantitative methodology with a cross-sectional design. This study comprised 60 toddlers who satisfied the inclusion criteria. The SQ-FFQ questionnaire gathered information regarding food consumption, the timing of complementary feeding was acquired through interview, and birth length was taken from the MCH book. The nutritional status of toddlers was assessed using the WHO Anthro program, and the results were analyzed employing the α= 5% contingency coefficient test.Results: A correlation was identified between energy intake and the incidence of stunting in Mojoketo (p-value = 0,039). However, no association was found between the timing of complementary feeding and birth length with the incidence of stunting in Mojokerto (p-value = 0,235, p-value = 0,445).Conclusion: Energy intake correlates with stunting in toddlers in Mojokerto. The timing of complementary feeding and birth length were not correlated with stunting in Mojokerto.